الجزاءات الادارية العامة: دراسة مقارنة - العاني وسام صبار (Journal of Legal Sciences, 2019)
The general administrative sanctions from the sanctions ,which recently emerged to confront some of the crimes that do not deserve to face criminal sanctions due to the lack of seriousness and gravity in the eyes of society, but enough to face sanction administrative general expectation administration without resorting to the judiciary, characterized by administrative sanctions public bmatiha own are in- dividual administrative decision issued by the administration punish- ment for violation of certain laws and regulations, which makes it a separate entity from all other forms of sanctions, the general admin- istrative sanctions (fines and confiscation) of others and sanctions financial (withdrawal of the license, stop the activity, the closure of the facility, administrative removal, publication of the judgment, expel and keep foreign).